Development of prediction models for carbapenem-resistant Klebsiella pneumoniae acquisition and prognosis in adult patients - Huijuan Yao; Yu Yang; Huimin Yao; Shuhong Bu; Lixia Li; Fang Wang; Jian Zhang; Jihui Chen (Frontiers in Pharmacology)
ObjectivesTo explore the risk factors and clinical outcomes of carbapenem-resistant Klebsiella pneumoniae (CRKP) infection and establish nomograms to predict the probability of CRKP infection and mortality in adult patients.MethodsPatients infected with KP from August 2019 to April 2021 in a tertiary hospital in Shanghai were enrolled. Risk factors associated with CRKP and 30-day mortality were identified using multivariate logistic regression analysis and Cox regression analysis.ResultsOverall, 467 patients with KP infection were enrolled, wherein 210 (45.0%) patients were infected with CRKP and 257 (55.0%) patients with carbapenem-susceptible K. pneumoniae (CSKP). Five factors, namely Charlson’s Comorbidity Index (CCI) ≥ 3, the use of central venous catheterization, prior hospitalization during the 3 months before infection, and previous exposure to carbapenems and broad-spectrum β-lactams, were found to be independently associated with CRKP infection. Based on these parameters, the nomogram showed a better performance as indicated by C-index of 0.94 (95% confidence interval [CI]: 0.92–0.96) and well-fitted calibration curves. CRKP was independently associated with 30-day mortality. Multivariate Cox regression analysis revealed that age ≥65 years, higher CCI scores, higher Sequential Organ Failure Assessment scores, the presence of respiratory failure, albumin levels ≤30 g/L, and non-appropriate treatments in 3 days, were associated with 30-day mortality.ConclusionThe predictive nomogram established in this study can facilitate the clinicians to make better clinical decisions when treating patients with KP infection.